The Effect of Health Promotion through Video Media on HIV/AIDS Stigma among Adolescents - Haris, Nursani A; Astuti, Dhesi Ari (Universitas Airlangga, 2025)
Background: HIV/AIDS is both a health and social issue, as its spread is heavily influenced by people's behaviors and knowledge. According to WHO data from 2022, 20 million adolescent females and 17.4 million adolescent males were infected with HIV. Meanwhile, data from the Indonesian Ministry of Health (Kemenkes RI) in 2022 reported that 741 adolescents were diagnosed with HIV. In its efforts to combat HIV/AIDS, the Indonesian Ministry of Health is committed to achieving the